GEOID-QUASIGEOID CORRECTION IN FORMULATION OF THE FUNDAMENTAL FORMULA OF PHYSICAL GEODESY - Tenzer, Robert; Vaníček, Petr (Revista Brasileira de Cartografia, 2006)
To formulate the fundamental formula of physical geodesy at the physical surface of the Earth, the gravity anomalies are used instead of the gravity disturbances, because the geodetic heights above the geocentric reference ellipsoid are not usually available. The relation between the gravity anomaly and the gravity disturbance is defined as a product of the normal gravity gradient referred to the telluroid and the height anomaly according to Molodensky's theory of the normal heights (Molodensky, 1945; Molodensky et al., 1960). Considering the normal gravity gradient referred to the surface of the geocentric reference ellipsoid, this relation is redefined as a function of the normal height (VaníÄek et al., 1999). When the orthometric heights are practically used for the realization of the vertical datum, the geoid-quasigeoid correction is applied to the fundamental formula of physical geodesy to determine the precise geoid.Theoretical formulation of the geoid-quasigeoid correction to the fundamental formula of physical geodesy can be found in Martinec (1993) and VaníÄek et al. (1999). In this paper, the numerical investigation of this correction at the territory of Canada is shown and the error analysis is introduced.